The Modificated of Automatic Feeder for Increasing Effectiveness of Fish Meal in Take - Jumalli, Selamat; Tang, Usman M; ', Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from January until March, 2013 in the pond experiment of Fisheries and Marine Science Faculty of Riau University, Pekanbaru. The purpose of this research was to improve the effectiveness of the tool automatic feeder in feeding on aquaculture. The method used was direct observation method and the treatments descriptive analyzes. Treatments were : low (8 volt), mid (10 volt), and hight (12 volt). The best results in the treatment of hight (12 volt) quantity feed out 620 – 648 grams, the distance issues feed 2,5 – 3,0 m and the level of error granting feed 0,74 %.Keywords : Automatic Feeder, Modification, Feeding